Screening for microsatellite instability target genes in colorectal cancers. Issue 11 (1st November 2002) - Vilkki, S; Launonen, V; Karhu, A; Sistonen, P; Västrik, I; Aaltonen, L A
Abstract : Background: Defects in the DNA repair system lead to genetic instability because replication errors are not corrected. This type of genetic instability is a key event in the malignant progression of HNPCC and a subset of sporadic colon cancers and mutation rates are particularly high at short repetitive sequences. Somatic deletions of coding mononucleotide repeats have been detected, for example, in the TGFβRII and BAX genes, and recently many novel target genes for microsatellite instability (MSI) have been proposed. Novel target genes are likely to be discovered in the future. More data should be created on background mutation rates in MSI tumours to evaluate mutation rates observed in the candidate target genes. Methods: Mutation rates in 14 neutral intronic repeats were evaluated in MSI tumours. Bioinformatic searches combined with keywords related to cancer and tumour suppressor or CRC related gene homology were used to find new candidate MSI target genes. By comparison of mutation frequencies observed in intronic mononucleotide repeats versus exonic coding repeats of potential MSI target genes, the significance of the exonic mutations was estimated. Results: As expected, the length of an intronic mononucleotide repeat correlated positively with the number of slippages for both G/C and A/T repeats (p=0.0020 and p=0.0012, respectively). BRCA1, CtBP1, and Rb1 associated CtIP and other candidates were found in a bioinformatic search combined with keywords related to cancer. Sequencing showed a significantly increased mutation rate in the exonic A9 repeat of CtIP (25/109=22.9%) as compared with similar intronic repeats (p≤0.001). Conclusions: We propose a new candidate MSI target gene CtIP to be evaluated in further studies.